Analysis of the Impact of Competency Certification on Improving Hotel Employee Performance in the Priority Tourism Destination Bromo Tengger Semeru (DPP-BTS): (Case Study of Hotel Front Office Clerks) - Ramansyah Hidayat; Retno Susanti; Kun Setiono; Sumarno Sumarno; Dwi Nisa; Nyoman Sumitra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to analyze the impact of competency certification in improving the quality of employees in the hotel front office department in the Priority Tourism Destination area of Bromo, Tengger, Semeru (DPP-BTS). In the hotel industry, improving service quality is an important focus to ensure guest satisfaction. In the midst of increasingly fierce competition, competency certification has been identified as a factor that has the potential to strengthen employee qualifications and performance, especially in the front office. The research method was carried out through a case study approach on a number of front office officers in superior hotels. Data collection was carried out through surveys, interviews and observations, to evaluate the level of competency related to certification and its impact on improving the quality of services provided by employees. The analysis's findings demonstrate that competence certification significantly raises the caliber of workers at the hotel front desk division. These findings indicate that employees who have been certified have a greater level of skill, knowledge and understanding of the best principles in providing service to guests, which in turn has a positive impact on guest satisfaction and experience. The implication of this research is that investment in competency certification for front office employees can be considered as an important strategy for hotel management to improve service quality. Practical recommendations include the development of more targeted certification programs, support from management for employee career development, and the integration of certification-related competencies into daily work practices in hotel front office departments. In conclusion, this research emphasizes the important role of competency certification in improving the quality of employees in hotel front offices, as well as offering valuable insights for decision makers in designing human resource development strategies to improve the quality of hotel services.